Effects of long‐term contrasting lime and phosphorus applications on barley grain yield, root growth and abundance of mycorrhiza. (25th August 2021) - Christensen, Julie Therese; Azeez, Musibau Oyeleke; Labouriau, Rodrigo; Ravnskov, Sabine; Kristensen, Hanne Lakkenborg; Munkholm, Lars Juhl; Rubæk, Gitte Holton
Summary: Lime and phosphorus (P) applications are common agricultural management practices. Our aim was to quantify the effects of long‐term application practices on root growth and abundance of arbuscular mycorrhizal fungi (AMF) under field conditions. We assessed the effects of lime and P fertilizer applications on barley yield, root growth and AMF abundance in 2016. Treatments were no, low, medium and high liming rate corresponding to application of 0, 4, 8 and 12 Mg lime ha −1 every 5–9 years since 1942 combined with no or yearly application of 15.6 kg P ha −1  since 1944. At harvest, grain yield, root intensity (core‐break) and AMF abundance at different soil depths were estimated. Root development was monitored during early growth with minirhizotrons in treatments receiving low, medium and high liming rates and P fertilization. A quadratic model relating grain yield to liming rate estimated yields to peak at 6.4 Mg lime ha −1 with yields of 4.2 and 3.2 Mg grain ha −1 with and without P fertilization, respectively. Low and medium liming rates resulted in greater AMF abundance, especially in the no P treatments. During early growth in P‐fertilized treatments, 77% and 65% more roots developed in the soil profile when treated with medium and high liming rate, respectively, compared to low liming rate. We conclude that long‐term application of lime in soils receiving yearly P fertilization improved conditions for root growth in soil layers below 30 cm, but at the high liming rate, this did not translate into higher yield.